2018
DOI: 10.1136/annrheumdis-2018-213902
|View full text |Cite
|
Sign up to set email alerts
|

Treat to target (drug-free) inactive disease in DMARD-naive juvenile idiopathic arthritis: 24-month clinical outcomes of a three-armed randomised trial

Abstract: QuestionWhich is the best strategy to achieve (drug-free) inactive disease in juvenile idiopathic arthritis (JIA)?MethodsIn a randomised, single-blinded, study in disease-modifying anti-rheumatic drug (DMARD)-naive patients with JIA, three treatment-strategies were compared: (1) sequential DMARD-monotherapy (sulfasalazine or methotrexate (MTX)), (2) combination therapy MTX + 6 weeks prednisolone and (3) combination therapy MTX +etanercept. Treatment-to-target entailed 3-monthly DMARD/biological adjustments in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
40
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(41 citation statements)
references
References 42 publications
0
40
0
1
Order By: Relevance
“…At baseline, all patient characteristics were acquired in a standardized manner, but clinical follow-up by the paediatric rheumatologist was not standardized and the investigators had no influence on the timing and data collection of follow-up. This limitation is compensated by cohort II, which consisted of patients participating in the trial; thus all data were prospectively acquired, following the standardized trial protocol [ 16 ], and our data show comparable results for both cohorts.…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…At baseline, all patient characteristics were acquired in a standardized manner, but clinical follow-up by the paediatric rheumatologist was not standardized and the investigators had no influence on the timing and data collection of follow-up. This limitation is compensated by cohort II, which consisted of patients participating in the trial; thus all data were prospectively acquired, following the standardized trial protocol [ 16 ], and our data show comparable results for both cohorts.…”
Section: Discussionmentioning
confidence: 94%
“…For example, regarding response to therapy, few patients could be categorized as responders to treatment in cohort I (10 out of 32 patients after 12 months of treatment), although in cohort II, 66 out of 81 patients were categorized as responders to therapy after 12 months. These numbers clearly demonstrate that the patients in cohort I and II were not similar: the latter cohort consisted of patients participating in a multicentre medication strategy trial [ 16 ]. These patients were younger in age, mainly from the poly-RF– subtype and had a shorter symptom duration and higher disease activity as compared with cohort I, which consisted of non-systemic JIA patients that were seen on our outpatient department and consented to participate in the study.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have recently performed a randomized clinical trial using the treatment-to-target approach in recent-onset JIA patients, comparing 3 strategy-arms with different initial and subsequent treatment steps, aiming at inactive disease, including tapering and stopping DMARD therapy [10, 11]. In this population we studied radiographic wrist damage using the Poznanski-score, at baseline and evaluated whether damage occurred or recovered with the abrogation of inflammation in the 3 strategy-arms.…”
Section: Introductionmentioning
confidence: 99%
“…A RD has also promised to provide readers with actual data for all data points in all figures in articles on clinical trials 1. This is in the process of implementation, as can be seen already in some trial papers published in recent months; the data are shown either directly in the publication (such as in ref 9) or in supplementary materials (such as in ref 10). We sincerely hope that in the future—thinking the thinkable—no publication on clinical trials in any journal will show figures without revealing the data for all data points.…”
mentioning
confidence: 98%